Measuring macro kinematics of classical cross-country skiing during on-snow training using a single micro-sensor unit - Marsland, F.; Mackintosh, C.; Anson, J.; Lyons, K.; Waddington, G.; Chapman, D. W. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Recent studies by Marsland et al. (2012) and Myklebust et al. (2014) highlighted the potential for micro-sensors in the identification and classification of cross-country skiing techniques. The advantage of micro-sensors for kinematic measurement is the possibility for continuous data collection during daily training and in competition. This study used micro-sensors to measure classical cross-country skiing macro kinematics in the field and determine their accuracy against simultaneously captured video footage.